Addiction, Anhedonia, and Comorbid Mood Disorder. A Narrative Review - Destoop, Marianne; Morrens, Manuel; Coppens, Violette; Dom, Geert (Frontiers in Psychiatry, 2019)
Background: Recently, anhedonia has been recognized as an important Research Domain Criterion (RDoC) by the National Institute of Mental Health. Anhedonia is proposed to play an essential role in the pathogenies of both addictive and mood disorders, and possibly their co-occurrence with a single individual. However, up to now, comprehensive information about anhedonia concerning its underlying neurobiological circuitries, the neurocognitive correlates, and their role in addiction, mood disorder, and comorbidity remains scarce. Aim: In this literature review of human studies, we bring together the current state of knowledge with respect to anhedonia in its relationship with disorders in the use of substances (DUS) and the comorbidity with mood disorders. Method: A PubMed search was conducted using the following search terms: (Anhedonia OR Reward Deficiency) AND ((Drug Dependence OR Abuse) OR Alcohol OR Nicotine OR Addiction OR Gambling OR (Internet Gaming)). Thirty-two articles were included in the review. Results: Anhedonia is associated with substance use disorders, and their severity is especially prominent in DUS with comorbid depression. Anhedonia may be both a trait and a state dimension in its relation to DUS and tends to impact DUS treatment outcome negatively.